If every company is adopting web services... why are so many failing?. - Esposito, Nancy (SOA webservices journal.)
Like most companies, you want to streamline your business, automate manual processes and expose key functionality to partners and customers. And like most companies, you probably have a mixture of applications and hardware-some new, some old.